Penerapan Metode Extreme Programming Pada Rancang Bangun Website Company Profile - Sarah Astiti (STMIK Budi Darma, 2023)
Today's website is something that cannot be separated from the development of the world of technology and the internet. The website has been used by almost all groups and almost all agencies that exist today. One of the benefits of the website is as a medium for delivering technology-based information, both in its application in the fields of government, education, health or in the business sector. Ahass Nusantara jaya is an official Honda partner repair shop located on Jl. General Gatot Subroto, Kebondalem, Purwokerto Lor, Kec. Purwokerto Team, Banyumas Regency. Currently, ahass archipelago jaya, in the process of implementing its business, whether in managing data services or managing spare parts data, still uses ledger records, this often results in errors in recording service data and spare parts data. Then when the customer wants to buy a type of spare part, the workshop admin or officer takes a long time to find the availability of the item. Based on these problems, a website is created that can help solve the problems described above by using the Extreme Programming (XP) method, then using the Unified Modeling Language (UML) in software modeling. . The XP method is used in this study, because this method is often used in designing systems that are not too large in nature, besides that the XP method is also considered a fast and efficient method. From the results of the research that has been carried out by implementing system testing using the blackbox functional method, the result is that the website company profile ahass archipelago jaya runs according to the design that has been made and can be used by the admin in managing service data and motorbike spare parts. In addition, customers can also access the company profile website for ahass nusantara jaya to find information related to Janis, the types of spare parts provided, and can also find information on the process of servicing motors that are being carried out by ahass nusantara jaya mechanics.